2021
DOI: 10.1007/s00376-021-1229-1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Cold Events from East Asia to North America in Winter 2020/21: Comparisons, Causes, and Future Implications

Abstract: Three striking and impactful extreme cold weather events successively occurred across East Asia and North America during the mid-winter of 2020/21. These events open a new window to detect possible underlying physical processes. The analysis here indicates that the occurrences of the three events resulted from integrated effects of a concurrence of anomalous thermal conditions in three oceans and interactive Arctic-lower latitude atmospheric circulation processes, which were linked and influenced by one major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…The results of this study are consistent with those of our previous study (Si et al, 2021), which shows that the IOCP is the most direct and important atmospheric pattern responsible for extreme cold waves in East Asia in January 2016. The influences of SSW on this extreme cold wave in East Asia have also been confirmed by other studies (Zhang et al, 2021a;Yu et al, 2022). Moreover, the tropospheric dynamics also played an important role in the occurrence of this extreme cold wave.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The results of this study are consistent with those of our previous study (Si et al, 2021), which shows that the IOCP is the most direct and important atmospheric pattern responsible for extreme cold waves in East Asia in January 2016. The influences of SSW on this extreme cold wave in East Asia have also been confirmed by other studies (Zhang et al, 2021a;Yu et al, 2022). Moreover, the tropospheric dynamics also played an important role in the occurrence of this extreme cold wave.…”
Section: Discussionsupporting
confidence: 75%
“…The SSW event and displacement of the stratospheric polar vortex may be attributed to the increase in the poleward transient eddy heat transport in the troposphere. A poleward propagating Rossby wave on 26-28 December 2020 resulted in a heat intrusion from the North Atlantic into the Arctic region (Zhang et al, 2021a). The poleward heat intrusion excited a strong tropospheric Rossby wave propagating from the troposphere to the midstratosphere in late December 2020 (Fig.…”
Section: The Ssw Event and Its Possible Causementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that before 15 January 2021, negative AO anomaly consistent with a weakened stratospheric polar vortex is responsible for cold events over East Asia (Zhang et al, 2021;Zheng et al, 2021), and its AC reached the minimum on 15 Jan 2021, which is speculated to be related to sign changes in the Asian SAT anomaly. In addition to the considerable contribution of Arctic stratospheric signals, winter climate variations over Asia can also be affected by variabilities in the tropical Pacific and North Atlantic sea surface temperature and the Arctic sea-ice concentration (e.g., Cheung et al, 2016Cheung et al, , 2018Yu et al, 2021;Zhang et al, 2021). As a result, the influence of other factors on changes in AC anomalies of SAT in Asia needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al (2022a) first pointed out that the middle-and high-latitude, large-scale atmospheric circulation anomalies associated with the negative phase of the North Atlantic Oscillation (NAO), a strengthened Siberian High, an intensified Ural High, and a deepened East Asian Trough, were the direct reasons for the frequent cold surges in winter 2020/21. The analysis by Zhang et al (2022a) further indicated that the occurrences of the three striking and impactful extreme cold weather events across East Asia and North America during the mid-winter of 2020/21 resulted from the integrated effects of a concurrence of anomalous thermal conditions in three ocean basins and an interactive Arctic-lower latitude atmospheric circulation process, which were linked through and influenced by one major sudden stratospheric warming (SSW) event. Zhang et al (2022b) also demonstrated the major SSW event occurred at the beginning of January 2021 exerted an important influence on the extreme cold wave in East Asia through inducing the stratospheric warming signal to propagate downward to the middle to lower troposphere, which not only enhanced the Urals-Siberia blocking and the negative phase of Atlantic Oscillation (AO), but also shifted the tropospheric polar vortex off the pole.…”
mentioning
confidence: 99%